Comparative Analysis of Indihome and Starlink Network Performance at the Banda Aceh City Office Ookla - M Ulul Azmy; Firmansyah (Jurnal Teknologi Informatika dan Komputer, 2026)
The availability of a fast, stable, and reliable internet network is a crucial factor in supporting office operational activities in the digital era. This study aims to analyze and compare the performance of the IndiHome and Starlink networks in the Banda Aceh City Office environment using the Ookla Speedtest application as the main measuring tool. The research method used is a quantitative approach with a comparative descriptive design. Data collection was carried out through direct network speed testing and the distribution of Likert-based questionnaires to 10 IndiHome office staff. The evaluation approach in this study focused on measuring internet network service quality parameters, such as access speed and delay to objectively assess the performance of IndiHome and Starlink services. Parameters analyzed include download speed, upload speed, latency, network stability, weather effects, ease of installation, and service costs. The results showed that the IndiHome network achieved a success rate of 96%, while the Starlink network achieved 95%, both of which are included in the very feasible category. However, based on Ookla testing results and user perceptions, the IndiHome network demonstrated more stable and consistent performance, even though both services have the same speed capacity of 300 Mbps. These findings indicate that the IndiHome network is more recommended as the primary internet connectivity solution to support office operational needs in Banda Aceh.